â€œCryocell-Cryocordâ€ at Complex Treatment of Patients with External Genital Endometriosis - Scherbina, M. A.; Potapova, L. V.; Scherbina, I. N.; Musatova, I. B. (Problems of Cryobiology and Cryomedicine, 2008)
There was studied the clinical efficiency of â€œCryocell-Cryocordâ€ preparation of cryopreserved serum of human cord blood at complex treatment of patients with endometriosis. It has been shown that the application of preparation normalizes the function of immune system, reduces organism sensitization of endometrial tissue antigens, and suppresses an inflammatory reaction.